Quantification of the sediment up to the misbaque dam site and its distribution in the reservoir - Rivero Solorzano, Jacinto (Revista Universidad de Guayaquil, 1991)
The evaluation of the sediment potential of the Paján River Basin up to the Misbaque Dam site is presented, which involves methodologies based on sediment sources, regional sampling and direct measurements. Based on what has been said, the distribution of the sediment is estimated and the height of the silt at the foot of the Dam is established.